2021
DOI: 10.1017/s0022215121002826
|View full text |Cite
|
Sign up to set email alerts
|

Superior semicircular canal dehiscence: a narrative review

Abstract: Background Described just over 20 years ago, superior semicircular canal dehiscence remains a relatively unknown and easily missed cause of dizziness and auditory symptoms. Objective This review focused on the origin, presenting symptoms and underlying pathophysiology of superior semicircular canal dehiscence, and the available treatment options. Main findings and conclusion The bony dehiscence acts as a ‘third window’, affecting inner-ear homeostasis, and resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…Although the exact etiology of SSCD is unclear, it is thought that both primary and secondary factors are involved. The presence of a thin segment of bone overlying the superior semicircular canal is a strong predisposing factor for SSCD following a trauma to the head or increased inner-ear pressure [ 2 , 10 12 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the exact etiology of SSCD is unclear, it is thought that both primary and secondary factors are involved. The presence of a thin segment of bone overlying the superior semicircular canal is a strong predisposing factor for SSCD following a trauma to the head or increased inner-ear pressure [ 2 , 10 12 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Superior semicircular canal dehiscence (SSCD) is characterized by loss of the bone overlying the superior semicircular canal of the inner ear and was first described by Minor and colleagues in 1998 [ 1 ]. Patients presenting with SSCD often experience hearing loss, disequilibrium, autophony, oscillopsia, and noise-induced vertigo [ 1 , 2 ]. Cadaveric studies have shown that SSCD has an approximate incidence of 0.7% [ 3 ], while radiological studies have reported an incidence rate of 3–9%, making SSCD a relatively rare disorder [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Superior semicircular canal dehiscence (SSCD) is caused by a thinning or absence of the bone overlying the superior semicircular canal ( Minor et al., 1998 ; Kontorinis and Lenarz, 2022 ). The area of dehiscence is believed to cause a “third window” which results in a loss in the conduction of mechanical energy through the labyrinth upon sound and pressure stimulation ( Kontorinis and Lenarz, 2022 ). Initially described by Minor et al.…”
Section: Introductionmentioning
confidence: 99%
“…Initially described by Minor et al. (1998) , SSCD can lead to a variety of otologic and vestibular symptoms including disequilibrium, autophony, hyperacusis, aural fullness, hearing loss, tinnitus, and vertigo ( Kontorinis and Lenarz, 2022 ; Naert et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%